2020
DOI: 10.1088/1361-6560/ab5fee
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear-interaction correction for patient dose calculations in treatment planning of helium-, carbon-, oxygen-, and neon-ion beams

Abstract: In charged-particle therapy treatment planning, the patient is conventionally modeled as variable-density water, i.e. stopping effective density ρS, and the planar integrated dose distribution measured in water (PID) is applied for patient dose calculation based on path length scaling with the ρS. This approximation assures the range accuracy of charged-particle beams. However, it causes dose calculation errors due to water nonequivalence of body tissues in nuclear interactions originating from compositional d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…It was reported that a +4% difference was observed in IDDs for a 150-mm-thick layer of 40% K 2 HPO 4 [ 8 ], which the authors used for emulating bone. This effect of the nonequivalence of water and body tissues intensifies for heavier ions [ 33 ]. The dosimetric effect of the water nonequivalence in a patient may amount to 2.5% for extreme clinical cases in carbon-ion radiotherapy [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that a +4% difference was observed in IDDs for a 150-mm-thick layer of 40% K 2 HPO 4 [ 8 ], which the authors used for emulating bone. This effect of the nonequivalence of water and body tissues intensifies for heavier ions [ 33 ]. The dosimetric effect of the water nonequivalence in a patient may amount to 2.5% for extreme clinical cases in carbon-ion radiotherapy [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Once available, future efforts may then perform comprehensive beam characterization, experimental dosimetry and acquisition of cross-section measurements, and model improvements for neon ion beam transport and fragmentation processes, as is currently done at NIRS. 68 However, given current limitations of the HIT accelerator system, clinical application of neon ions may be limited with a maximum range under 18 cm in water. Nonetheless, the in-silico results of this work are promising and suggest potential clinical value for particle arc therapy using oxygen and neon ions for increasing LET in the target volume compared to carbon ions.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is ongoing discussion in‐house on whether supplementary heavy ion sources such as neon ions should be added to the three existing sources for protons, helium, and carbon/oxygen. Once available, future efforts may then perform comprehensive beam characterization, experimental dosimetry and acquisition of cross‐section measurements, and model improvements for neon ion beam transport and fragmentation processes, as is currently done at NIRS 68 . However, given current limitations of the HIT accelerator system, clinical application of neon ions may be limited with a maximum range under 18 cm in water.…”
Section: Discussionmentioning
confidence: 99%
“…To calculate the isoeffective dose distribution based on the OSMK model with (20)-( 24 ¯distributions of the beamlets in the patient with density scaling using the stopping power ratio of body tissues to water in each treatment plan (Inaniwa and Kanematsu 2016). For the calculations in the patient, the dose calculation errors due to water-nonequivalence of the body tissues in inelastic nuclear interactions were accounted for by the dedicated correction method (Inaniwa et al 2015a(Inaniwa et al , 2020a.…”
Section: Beam Modelingmentioning
confidence: 99%
“…A development project for hypo-fractionated multi-ion therapy (HFMIT) has been initiated at the National Institutes for Quantum Science and Technology (QST) in Japan for further improvement of clinical results of charged-particle therapy especially for radioresistant tumors. In the treatment, helium-, carbon-, oxygen-, and neon-ion beams will be used as primary beams with wide linear energy transfer (LET) ranges (Inaniwa et al 2020a(Inaniwa et al , 2020b(Inaniwa et al , 2021. To carry out the HFMIT, the biological effectiveness of these radiation beams has to be predicted for individual clinical cases based on biological models (Kanai et al 1999, Krämer and Scholz 2000, Inaniwa et al 2015c.…”
Section: Introductionmentioning
confidence: 99%